Salt-dependent interconversion of inner histone oligomers. - Butler, A P (1979)
The inner histone complex, extracted from chicken erythrocyte chromatin in 2 M NaCL AT pH 7.4, has been characterized by sedimentation equilibrium and sedimentation velocity. High speed sedimentation equilibrium studies indicate that in 2 M NaCl the inner histones are a weakly associating system with contributions from species ranging in molecular weight from dimer to octamer. The appearance of a single boundary (3.8S at 2 M NaCl) in sedimentation velocity studies conducted over a wide range of protein concentrations and ionic conditions indicates that the various histone oligomers present are in rapid equilibrium with one another. At higher salts the equilibrium is shifted to favor higher molecular weight species; in 4 M NaCl essentially all of the histone is octameric at protein concentrations above 0.2 mg/ml. The facile interconversion of histone oligomers suggests that small alterations in histone-histone interactions may be responsible for changes in nucleosome conformations during various biological processes.